Impact of Social Media in Learning EFL Iraqi Students New Words - NESRALLAH., Omar; MURAD ZANGANA, Ibtihal (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The study aims to investigate the impact of social media in improving students’ ability of English language, namely vocabulary acquisition with second year EFL students in University of Diyala. Social media technologies work on many different forms including magazines, internet forums, weblogs, social blogs, wikis, social networks, podcasts, pictures, videos etc. Several studies investigate the use of different technologies in learning and teaching, in particular, foreign language learning. Still, rare studies were interested precisely in the role of social media in learning foreign languages. This study assessed the role and effectiveness of social media use in vocabulary learning.